High central venous oxygen saturation is associated with mitochondrial dysfunction in septic shock: A prospective observational study - Borwon Wittayachamnankul (2020)
© 2020 The Authors. Journal of Cellular and Molecular Medicine published by John Wiley & Sons Ltd and Foundation for Cellular and Molecular Medicine. To test the hypothesis that an impaired mitochondrial function is associated with altered central venous oxygen saturation (ScvO2), venous-to-arterial carbon dioxide tension difference (delta PCO2) or serum lactate in sepsis patients. This prospective cohort study was conducted in a single tertiary emergency department between April 2017 and March 2019. Patients with suspected sepsis were included in the study. Serum lactate was obtained in sepsis, ScvO2 and delta PCO2 were evaluated in septic shock patients. Mitochondrial function was determined from the peripheral blood mononuclear cells. Forty-six patients with suspected sepsis were included. Of these, twenty patients were septic shock. Mitochondrial oxidative stress levels were increased in the high ScvO2 group (ScvO2 > 80%, n = 6), compared with the normal (70%-80%, n = 9) and low ScvO2 (<70%, n = 5) groups. A strong linear relationship was observed between the mitochondrial oxidative stress and ScvO2 (r =.75; P =.01). However, mitochondrial respiration was increased in the low ScvO2 group. In addition, mitochondrial complex II protein levels were significantly decreased in the high ScvO2 group (P <.05). Additionally, there was no correlation between serum lactate, delta PCO2, and mitochondria oxidative stress or mitochondria function. ScvO2 can be potentially useful for developing new therapeutics to reduce mitochondrial dysfunction in septic shock patient.